ORIENTASI PEMBINAAN KONSEP TRI SUKSES PENDIDIKAN ISLAM DALAM PARADIGMA PEMIKIRAN IBNU MISKAWAIH - Mohamad Maulidin Alif Utama; Ike Hillatun Nisa; Alexander Guci (STAI Tuanku Tambusai, 2022)
Starting from a question, why the behavior of most students comes out of good behavior while having understood moral education? This is because morality is only given seminars, notified, informed, not accustomed to, trained and given examples. Ibn Miskawaih emphasizes that behavior must be familiarized and trained, as is the case with tri-success guidance in which there is an alim (religious understanding) the orientation is understanding of basic obligations such as holy-unclean, lawful-haram and others, wise the orientation is good character, polite, and courteous in situations and conditions, while independent orientation is not relying on other people in any case, thus it must be familiarized, trained and given an example not just being told, informed and in seminars all oriented to the goals of Islamic education. Descriptive qualitative research method, this is carried out to build knowledge through understanding and discovery, the analysis used is data reduction, data presentation, drawing conclusions.